Development of an instrument for measuring activities of daily living in persons with suspected cognitive impairment. (3rd May 2016) - Johansson, Maria M.; Marcusson, Jan; Wressle, Ewa
ABSTRACT: Background According to the Swedish National Board of Health and Welfare, structured assessment of function and activity has high priority when evaluating suspected cognitive impairment or dementia.Aim/objectives The aim was to develop and psychometrically test an instrument to measure the ability to perform activities of daily living tasks in patients with suspected cognitive impairment.Material and methods The Cognitive Impairment in Daily Life (CID) instrument (for self-reported and informant-based assessments) has been developed in several phases. Content validity was achieved through five expert panels using a Content Validity Index (CVI). The content was tested further in a pilot study of 49 patients and 49 relatives from primary care or a specialist memory clinic.Results Content validity was good with a CVI index of 0.83. All patients considered that the included activities were relevant to them and reflected the difficulties they were experiencing. Most relatives considered the activities included in the instrument as adequate and captured the patients' difficulties in daily life. Some adjustments of the tasks and scale were suggested and these were implicated after each phase. In general, relatives reported that patients had more difficulties performing the activities than the patients reported themselves.Conclusion The CID instrument seems promising in terms of content validity. Further testing of reliability and construct validity is ongoing.